2021
DOI: 10.3390/met11081321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Strain on Microstructure and Tensile Properties of Ti-6Al-4V at Elevated Temperature

Abstract: Research on pre-deformation influences on material properties in multistep hot forming is of important scientific interest. In this paper, hot tensile tests at 850 °C and a strain rate of 0.001 s−1 were performed to study the microstructural evolution and mechanical properties of Ti-6Al-4V with pre-strains at 0.05, 0.1 and 0.15. The tensile test results showed that the specimen with 0.05 pre-strain exhibited higher flow stress and larger elongation. Additionally, increasing the pre-strain resulted in a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…One of the primary benefits of L-PBF is its effective utilization of materials, resulting in a reduction of material waste compared to conventional manufacturing techniques [104,107]. L-PBF is a manufacturing technique that employs selective melting of specific regions within the powder bed, thereby reducing material consumption and minimizing waste generation [105].…”
Section: Materials Utilization and Waste Generationmentioning
confidence: 99%
“…One of the primary benefits of L-PBF is its effective utilization of materials, resulting in a reduction of material waste compared to conventional manufacturing techniques [104,107]. L-PBF is a manufacturing technique that employs selective melting of specific regions within the powder bed, thereby reducing material consumption and minimizing waste generation [105].…”
Section: Materials Utilization and Waste Generationmentioning
confidence: 99%
“…They found its gradual softening with an increase in deformation temperature in the range of 500-1000 • C to be associated with the dynamic recovery and recrystallization processes, in addition to the reorientation and shortening of TiB whiskers. The effect of pre-deformation on the hot plasticity of Ti-6Al-4V alloy was researched by Wu et al [3]. It was found that pre-strain of 0.05 enhanced flow stress and elongation in tensile tests at a temperature of 850 • C. Moreover, pre-strain promoted dynamic recrystallization by increasing the deformation substructure.…”
Section: Deformation Behaviormentioning
confidence: 99%
“…Owing to its exceptional combination of high specific strength, low density, and excellent corrosion resistance, among other advantages, the Ti-6Al-4V alloy finds extensive applications in aviation, medical, automotive, and various other industries [1][2][3]. Over the 80 years since its discovery, superplasticity refers to the performance of a material that can achieve large elongation without fracture in a specific temperature and strain rate range [4,5].…”
Section: Introductionmentioning
confidence: 99%